2013
DOI: 10.1016/j.febslet.2013.01.009
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of the cysteine protease Xylellain from Xylella fastidiosa reveals an intriguing activation mechanism

Abstract: a b s t r a c tXylella fastidiosa is responsible for a wide range of economically important plant diseases. We report here the crystal structure and kinetic data of Xylellain, the first cysteine protease characterized from the genome of the pathogenic X. fastidiosa strain 9a5c. Xylellain has a papain-family fold, and part of the N-terminal sequence blocks the enzyme active site, thereby mediating protein activity. One novel feature identified in the structure is the presence of a ribonucleotide bound outside t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Structural features of Lpg2622. (A) Superimposed structures of Lpg2622 (colored in green), Xylellain (colored in wheat, PDB : 3OIS) , and propapain (colored in lightblue, PDB : 3TNX) . (B) Superimposed structures of the core catalytic domain and the catalytic residues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural features of Lpg2622. (A) Superimposed structures of Lpg2622 (colored in green), Xylellain (colored in wheat, PDB : 3OIS) , and propapain (colored in lightblue, PDB : 3TNX) . (B) Superimposed structures of the core catalytic domain and the catalytic residues.…”
Section: Resultsmentioning
confidence: 99%
“…In bacteria, two members of the C1 family peptidases have been structurally determined to date. One is the cysteine protease xylellain from xylella fastidiosa , which has a papain family fold and a short propeptide (56 residues), and part of the N‐terminal propeptide blocks the active site, thereby mediating enzyme activity . The other is cysteine protease Cwp84, a surface layer‐associated protein from Clostridium difficile , which comprises the cysteine protease domain, the identified lectin‐like domain and the propeptide .…”
mentioning
confidence: 99%
“…Since they are common in protist pathogens, we can infer that they probably play an important role in the host-pathogen arms race, most likely in host invasion. Additionally, the functions of bacterial ancestral-type short C1A peptidases are still scarce and limited to two species [70,71]. Three-dimensional structures are available for six eukaryotic ancestral paralogous C1A lineages, for cathepsins B [18], C [25], X [23], L/papain [17,20], F [27], and H [22], while no structures are available for the "insect 26/29 kDa peptidase" or the "type 1 long C1 peptidase", although highquality models can be obtained with AlphaFold [72] (Figure 3).…”
Section: Structure-function Relationships In the Papain Familymentioning
confidence: 99%
“…For evolutionarily younger eukaryotic C1A lineages (e.g., cathepsin O and vWFA-C1), highquality models can be easily produced using AlphaFold [72]. Crystal structures of the diverse eukaryotic [17,18,[20][21][22][23]25,27] and short prokaryotic [70,71] C1A peptidases have shown that their core catalytic machinery and fold is highly conserved throughout evo- Discovering the repertoire of ancestral eukaryotic C1A peptidases is important for directing structural studies of the papain family, as its structural diversity in eukaryotes is already well-known. Even in prokaryotes, two 3D structures are available for singledomain (or short) C1A peptidases [70,71], and one structure is available for multidomain C1A peptidase, where the lectin domain is fused with the C1A domain [74].…”
Section: Structure-function Relationships In the Papain Familymentioning
confidence: 99%
See 1 more Smart Citation